The Political Economy of Datafication and Platformization: Digital Transformation in Higher Education - Komljenovic, Janja; Williamson, Ben (International Higher Education, 2025)
<h3 id="platforms-data-and-artificial-intelligence-ai-are-impacting-higher-education-systems-and-universities-internationally-they-raise-challenges-including-locking-in-institutions-to-corporate-technologies-monetizing-data-and-interfering-with-academic-governance-future-research-is-required-to-examine-the-concrete-effects-of-platforms-data-and-ai-in-context-specific-settings-and-to-understand-their-underpinning-political-economy-and-future-impact-on-international-education-and-its-constituents" data-pm-slice="1 1 []">Platforms, data, and artificial intelligence (AI) are impacting higher education systems and universities internationally. They raise challenges, including locking in institutions to corporate technologies, monetizing data, and interfering with academic governance. Future research is required to examine the concrete effects of platforms, data, and AI in context-specific settings, and to understand their underpinning political economy and future impact on international education and its constituents.